2022
DOI: 10.1017/s0954579422000906
|View full text |Cite
|
Sign up to set email alerts
|

Using genetic designs to identify likely causal environmental contributions to psychopathology

Abstract: The multifactorial nature of psychopathology, whereby both genetic and environmental factors contribute risk, has long been established. In this paper, we provide an update on genetically informative designs that are utilized to disentangle genetic and environmental contributions to psychopathology. We provide a brief reminder of quantitative behavioral genetic research designs that have been used to identify potentially causal environmental processes, accounting for genetic contributions. We also provide an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…Genetically-informed, two-generation research studies have endeavored to isolate genetic and environmental contributions to the intergenerational transmission of multiple behaviors and characteristics from G2 to G3, by addressing shared genetic and environmental confounds (reflected in gene-environment correlations; see Sellers et al, 2022). A genetically-informed threegeneration design could be developed by continuing to follow prospective twin cohorts (e.g., ABCD twin subsample; Fan et al, 2023) into parenthood, as an extension of the children of twins (CoT) design (see McAdams et al, 2018;Sellers et al, 2022). In this framework, G2 twins would be followed longitudinally, beginning in childhood with their G1 parent(s) and then with their G3 children.…”
Section: Disentangling Genes and Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetically-informed, two-generation research studies have endeavored to isolate genetic and environmental contributions to the intergenerational transmission of multiple behaviors and characteristics from G2 to G3, by addressing shared genetic and environmental confounds (reflected in gene-environment correlations; see Sellers et al, 2022). A genetically-informed threegeneration design could be developed by continuing to follow prospective twin cohorts (e.g., ABCD twin subsample; Fan et al, 2023) into parenthood, as an extension of the children of twins (CoT) design (see McAdams et al, 2018;Sellers et al, 2022). In this framework, G2 twins would be followed longitudinally, beginning in childhood with their G1 parent(s) and then with their G3 children.…”
Section: Disentangling Genes and Environmentsmentioning
confidence: 99%
“…Briefly, as a form of family-based, quasi-experimental design, CoT studies allow for tests of competing causal hypotheses based on differences in the degree to which family members share genes and environments (for detailed discussion, see Sellers et al, 2022;Wilson & Rhee, 2022). Children of monozygotic (MZ) twins are as genetically related to their parent as there are their parent's cotwin, with 50% of their genes shared.…”
Section: Disentangling Genes and Environmentsmentioning
confidence: 99%
“…In their comprehensive overview of genetically informative approaches, Sellers et al (2022) describe many of the study designs used by papers in this Special Issue, highlighting the critical role of these approaches for understanding genetic and environmental influences on the etiology and course of psychopathology. In particular, they emphasize the potential for "genetic confounding" on putative environmental factors and the advantages of genetically informative approaches for elucidating potentially causal environmental processes in the development and familial transmission of psychopathologyafter accounting for genetic influences.…”
Section: Genetically Informative Approaches To the Development And Fa...mentioning
confidence: 99%
“…For decades, family‐based designs have been helping to establish the importance of environmental influences on psychopathology. For example, they have shown that a substantial portion of variance in psychopathology is due to environmental influences, and demonstrated the impact of specific environmental factors – such as parenting or parental mental health – on offspring psychopathology, over and above genetics shared between the parent and child (Sellers, Riglin, Harold, & Thapar, 2022). Combining these methods with molecular‐genetic data offers even more ways to investigate environmental effects.…”
mentioning
confidence: 99%